Identification of a novel nucleolar protein complex required for mitotic chromosome segregation through centromeric accumulation of Aurora B. Issue 12 (1st June 2020) - Fujimura, Akiko; Hayashi, Yuki; Kato, Kazashi; Kogure, Yuichiro; Kameyama, Mutsuro; Shimamoto, Haruka; Daitoku, Hiroaki; Fukamizu, Akiyoshi; Hirota, Toru; Kimura, Keiji
Abstract: The nucleolus is a membrane-less nuclear structure that disassembles when cells undergo mitosis. During mitosis, nucleolar factors are thus released from the nucleolus and dynamically change their subcellular localization; however, their functions remain largely uncharacterised. Here, we found that a nucleolar factor called nucleolar protein 11 (NOL11) forms a protein complex with two tryptophan-aspartic acid (WD) repeat proteins named WD-repeat protein 43 (WDR43) and Cirhin in mitotic cells. This complex, referred to here as the NWC (NOL11-WDR43-Cirhin) complex, exists in nucleoli during interphase and translocates to the periphery of mitotic chromosomes, i.e., perichromosomal regions. During mitotic progression, both the congression of chromosomes to the metaphase plate and sister chromatid cohesion are impaired in the absence of the NWC complex, as it is required for the centromeric enrichment of Aurora B and the associating phosphorylation of histone H3 at threonine 3. These results reveal the characteristics of a novel protein complex consisting of nucleolar proteins, which is required for regulating kinetochores and centromeres to ensure faithful chromosome segregation.